Plasma Ascorbate Protects Coagulation Factors against Photooxidation - Parkkinen, Jaakko; Vääränen, Outi; Vahtera, Elina (Thrombosis and Haemostasis, 1996)
It has been suggested that proteins, unlike lipids, are not protected against oxidative damage by antioxidants in plasma. We have studied the effect of photodynamic virus inactivation treatment of fresh human plasma on coagulation factor activities. Photodynamic treatment generates singlet oxygen which causes inactivation of fibrinogen and factor VIII. Other coagulation factors or anticoagulant proteins are clearly less affected. We found that there is an inverse correlation between the extent of coagulation factor inactivation during the treatment and the plasma ascorbate concentration. The inactivation of coagulation factors was prevented in a dose-dependent manner by adding ascorbate to the plasma before the treatment. Ascorbate was consumed during the treatment at an apparently linear rate. Oxidation of urate and coagulation factors was enhanced when ascorbate had disappeared from plasma. These results indicate that ascorbate is a primary antioxidant against photooxidation in plasma and that it effectively prevents oxidative damage to coagulation factors and other proteins.